Effects of malocclusions on facial attractiveness and their correlations with the divine proportion - Akan, Seden; Torgut, Ayşe Gül; Oktay, Hüsamettin (Urban & Vogel, 2017)
The aim of this study was to evaluate the effects of malocclusions on facial attractiveness and to determine if it was correlated with the divine proportion. Standard frontal facial photos were taken from 335 subjects in natural head position. Facial attractiveness of the subjects was evaluated by 10 dental students using a 10-point visual analog scale (VAS). All of the evaluations were arranged in order, and 30 attractive subjects with the highest score and 30 nonattractive subjects having the lowest score were chosen. On the frontal photos of these subjects, 13 landmarks were determined and 12 ratios were measured. Two way ANOVA was used to determine the effects of malocclusions on facial attractiveness, Student's t test was used to compare the facial proportions of the attractive and nonattractive subjects, and one sample t test was used to define the relationships between the divine proportion and facial ratios. No statistically significant difference was found between malocclusion groups in terms of facial attractiveness. Of the 12 facial ratios, significant differences were found between attractive and nonattractive subjects regarding trichion-menton/nasion-menton, subnasale-menton/stomion-menton, nasion-subnasale/stomion-menton, nasion-subnasale/nasal width, and trichion-menton/right-left frontotemporale ratios. All of the ratios except nasion-subnasale/stomion-menton in the attractive group and subnasale-menton/stomion-menton and nasion-menton/nasion-trichion in the nonattractive group were found to be different from the divine proportion. Sagittal skeletal malocclusions evaluated by ANB angle are not effective on facial attractiveness. Facial ratios used in this study have little effect on attractiveness, and are different from the divine proportion.
WOS: 000408383500007
PubMed ID: 28451737
Keywords: Facial Proportion; Divine Proportion; Esthetic Perception; Malocclusions; Anthropometry